C.E.O. Characteristics and Corporate Risk-Taking: Evidence from Emerging Markets - Cid-Aranda, C (Taylor and Francis Ltd., 2023)
Although the Upper Echelon Theory predicts that C.E.O.s play a relevant role in corporate risk-taking, the C.E.O.s’ traits that can be associated with such risk are not well-explored. Our study fills this gap and shows the effect of C.E.O.s’ characteristics on corporate risk-taking of a hand-collected sample of 369 Latin American listed firms. We study six traits: C.E.O.s’ age, tenure, gender, duality (i.e., holding concurrent Chairman and C.E.O. roles), educational background, and career horizon. We find that age increases risk-taking. However, when the C.E.O. s age reaches a given point, their concern about reputation and retirement results in a negative relationship. We also find that as C.E.O. tenure increases, corporate risk begins to decrease. Nevertheless, there comes a point at which the C.E.O. uses their knowledge and their overconfidence to make risky financial decisions. Female C.E.O.s are negatively related to risk-taking, while C.E.O. duality, C.E.O. educational background, foreign C.E.O.s, and a C.E.O. s career horizon have the opposite effect. Our study is novel because of the focus on emerging markets and because of the use of different market-based measures of risk-taking. We provide policymakers, investors, and practitioners with fresh evidence about how C.E.O.s’ risk aversion shapes the firm’s risk-taking behaviour. © 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.